Luka Batin Tak Terlihat: Dampak Bullying pada Kesehatan Psikologis Siswa - Bunga Dahlia; Dania salsabilah Azzahra; Aurora Risqika Azzahra; Selfia Puspita Dewi; Fayzalisha Asheela Gunawan; Rijal Abdillah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Bullying is a phenomenon that has a serious impact on students' psychological health. This study aims to examine the impact of bullying on students' mental well-being, including stress, anxiety, and depression. The research method used was quantitative with a descriptive and correlational survey design, involving 35 respondents from high school students. The results showed that 57.14% of respondents had experienced bullying, with verbal forms being the most dominant (75%). The findings also revealed that bullying has a significant impact on students' mental health, with 71.43% of respondents reporting major psychological disorders. The conclusion of this study emphasizes the need for comprehensive efforts to prevent bullying in schools, through educational programs, anti-bullying policies, and social support.